Una apreciación a la comercialización de la producción minero metalúrgica en el Perú, periodo 1970-2010. - Ospino Edery, Juan José (2012)
This study develops a particular diagnosis that covers four periods of the evolution and implications of mining and metallurgical activity and marketing. The first period regulated by de mining code of 1950, which guided and impetus so liberal mining investment capital mainly American, a second period by the years 1968-1980, period during which the state assumed the role of promoter, performer and leader of the mining and metallurgical activity and marketing of monopoly in compliance with the General Mining Law 18880. A third period from 1980-1990, involving both the second administration of President Fernando Belaunde as first government of Alan Garcia, a stage during which remained the state´s role in relation to activity as a promoter and leader of mining activity, metal, varying only their role in the marketing monopoly of mining production. A fourth and final period is in effect, characterized by privatization of mining companies that were owned by the state thus extinguished their actions in the sale of ores, concentrates, melted and refined in practice back schemes mining and marketing similar to those promoted by the mining code of the fifties.